2009
DOI: 10.1093/pubmed/fdp107
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of smokers and predictors of quitting in a smoking cessation clinic in Guangzhou, China

Abstract: A pilot-model clinic free of charge and with systemic data collection, follow-up and evaluation should be a starting point for smoking cessation program in low-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 33 publications
5
35
1
Order By: Relevance
“…Similarly, regional studies (Jayakrishnan et al 2013;Zhu et al 2010) also showed that mean age started smoking were 15±8.28 and 20±5 years old respectively. This means that the smokers are more likely to have longer years of exposure to nicotine, and higher tendency to have nicotine addiction.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, regional studies (Jayakrishnan et al 2013;Zhu et al 2010) also showed that mean age started smoking were 15±8.28 and 20±5 years old respectively. This means that the smokers are more likely to have longer years of exposure to nicotine, and higher tendency to have nicotine addiction.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, there is a large variety in smokers seeking for quit advice across countries [50]. Smokers in middle-income countries generally reported lower-level use of quitting smoking medications and health professional services, but not necessarily less interest in quitting [51]. In addition, the high percentage of unaided quit attempts observed in those countries could be due to barriers for the use of support to quit smoking, e.g., financial reasons [52].…”
Section: Discussionmentioning
confidence: 99%
“…The fi rst smoking cessation clinic in Guangzhou, China ' s third largest city, was established only 6 years ago and had success similar to Western clinics (i.e., by intention to treat, the 6-month 7-day point prevalence quit rate was 24% [95% CI = 18 % -30%]). Smokers with more confidence in quitting or were at action stage were more successful in quitting ( W. H. Zhu et al, 2010 ). Despite this progress, more must be done.…”
Section: Introductionmentioning
confidence: 99%